Practical torso cooling during soccer-specific exercise in the heat - Parris, K.; Tyler, C. J. (Journal of Athletic Training, 2018)
Context: Precooling and midevent cooling of the torso using cooling vests can improve exercise performance in the heat with or without physiological changes; however, the effects of such cooling during intermittent exercise in the heat are unknown. Objective: To investigate the effects of torso cooling during intermittent exercise in the heat (35°C, 50% relative humdity) on sprint performance and the physiological and perceptual responses to the exercise.